2021
DOI: 10.2298/sarh200730006s
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized tuberculosis in a patient with COVID-19

Abstract: Introduction. COVID-19 is responsible for the current global pandemic. Globally, over 15 million people are currently infected, and just over 600,000 have died due to being infected. It is known that people with chronic illnesses and compromised immune systems can develop more severe clinical presentation. Tuberculosis is still one of the biggest epidemiological problems worldwide. Both of these diseases can be misdiagnosed and can manifest in a similar way. We will present a case study of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…In most studies, leukopenia, particularly lymphocytopenia, was reported. In contrast, neutrophilic leukocytosis was observed in some studies (Garg and Im Lee, 2020;Singh et al, 2020;Mishra et al, 2021;Stjepanović et al, 2021).…”
Section: Laboratory Criteriamentioning
confidence: 90%
“…In most studies, leukopenia, particularly lymphocytopenia, was reported. In contrast, neutrophilic leukocytosis was observed in some studies (Garg and Im Lee, 2020;Singh et al, 2020;Mishra et al, 2021;Stjepanović et al, 2021).…”
Section: Laboratory Criteriamentioning
confidence: 90%
“…Patients with chronic obstructive pulmonary disease and pulmonary emphysema are at higher risk of pneumothorax when infected with SARS-CoV-2 [19]. Signs suggestive of potential comorbidities on CRX might be obscured by signs of COVID-19 pneumonia [20]. However, in some cases, COVID-19 pneumonia changes might be so widespread that features suggestive of comorbidities are obscured.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear who, when or if will develop this complication. As of writing of this article, there are roughly 20 million infected people, with round 13 million who have recovered from COVID-19 infection [7,8]. How many of the recovered patients will have any complications, and if those complications are reversible, only time will tell.…”
Section: Discusionmentioning
confidence: 99%